СТАТИЈАТА „ГЛАВНИТЕ КВАЛИТЕТИ КОИ ТРЕБА ДА ГИ ПОСЕДУВА ЕДНА ДОБРА УЧИТЕЛКА-ВОСПИТУВАЧКА“ ОД ОЛГА МАЏАРОВА - Славчо Ковилоски (Институт за македонска литература, 2021)
Among the Macedonian authors who left their mark in the periodicals at the beginning of the 20th century, a sig nificant place belongs to Olga Madzarova (1887, Negovan, Thessaloniki area - Gorna Dzumaja after 1934). She is the author of the longest journalistic text in general, published by a Macedonian woman on the pages of the daily press in Macedonia under Ottoman rule, i.e. until 1912. Madzarova is the author of the article “The main qualities that a good teacher-pedagogue should possess”, published in two parts on the pages of The Vesti newspaper. The first part was published in issue 71 of July 30, 1904, and its sequel in issue 72 of August 3 of the same year. Under the title of the first part is the information: “Speech delivered by the student Olga Madzarova at the annual act of the Thessaloniki Women’s High School on June 37, 1904.” The two parts published in issues 71 and 72 of The Vesti newspaper refer to the importance of teachers in the education of girls, as well as to their role and presence in public life. The selected words used by the young author indicate the qualities that she possessed, and that she was able to express, in her own way, her thoughts full of hope and ideals for a better future.
Keywords: Olga Madzarova; The Vesti newspaper; 19th-20th century; Macedonian women’s writing; women question; women’s education